COMPARATIVE STUDY OF TERRITORIAL AND NATIONAL ACTIVE PRINCIPLES IN THE CONTEXT OF THE APPLICATION OF CRIMINAL LAW IN INDONESIA - Kusmiyati; Syamsuddin; Ilham (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
This study examines the comparison between the territorial principle and the active national principle in the context of criminal law enforcement in Indonesia. Indonesia, as a vast archipelagic country, faces challenges in the application of cross-border criminal law, especially in cases involving Indonesian citizens who commit crimes abroad and foreign citizens who commit crimes in their territory. The territorial principle focuses on the location of the crime, while the active national principle allows the prosecution of Indonesian citizens for crimes committed abroad. This study analyzes the legal framework stipulated in the 1946 Criminal Code (KUHP) and the revised version in 2023, highlighting the differences and implications of the two principles. Through normative legal research, this research aims to identify the effectiveness of these principles in dealing with transnational crime and emerging legal dilemmas. The findings of the study show that while both principles serve to uphold national sovereignty and protect the rights of citizens, their application can give rise to jurisdictional conflicts, which require international cooperation and legal harmonization.